2021
DOI: 10.1093/carcin/bgab067
|View full text |Cite
|
Sign up to set email alerts
|

USO1 isoforms differentially promote liver cancer progression by dysregulating the ER–Golgi network

Abstract: Alternative splicing of RNA transcripts plays an important role in cancer development and progression. Recent advances in RNA-seq technology have made it possible to identify alternately spliced events in various types of cancer; however, research on hepatocellular carcinoma (HCC) is still limited. Here, by performing RNA-Seq profiling of HCC transcripts at isoform level, we identified tumor-specific and molecular subtype-dependent expression of the USO1 isoforms, which we designated as a normal form USO1-N (X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…USO1 has been implicated in tumourigenesis in multiple cancers including gastric ( 10 ), colon ( 11 ), breast ( 12 ), liver cancer ( 13 ) as well as multiple myeloma ( 14 ) and leukaemia ( 38 ). Overexpression of USO1 has been shown to play a role in cell proliferation and cell cycle transition in these studies, and as such in general, one would expect high expression of USO1 to be associated with worse OS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…USO1 has been implicated in tumourigenesis in multiple cancers including gastric ( 10 ), colon ( 11 ), breast ( 12 ), liver cancer ( 13 ) as well as multiple myeloma ( 14 ) and leukaemia ( 38 ). Overexpression of USO1 has been shown to play a role in cell proliferation and cell cycle transition in these studies, and as such in general, one would expect high expression of USO1 to be associated with worse OS.…”
Section: Discussionmentioning
confidence: 99%
“…The exact reason for this remains to be elucidated and warrants further investigation. It may be that a tumour specific transcript of USO1 is a key element as recently described for hepatocellular carcinoma, where a specific mRNA variant USO1-T (RefSeq NM_003715.4, transcript variant 2) is associated with worse prognostic outcomes and an aggressive phenotype in HCC ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ERK and GRASP65 were found to be involved in the USO1-T-mediated Golgi dysfunction. 20 In another study, Golgi compaction was found in cells that had completed an Epithelial to Mesenchymal transition (EMT), driven by the scaffolding protein PAQR11. 21 Experimental evidence also indicates that ER and Golgi apparatus can activate both pro-survival (recovery) mechanisms as well as cell suicide programs if the stress-signaling threshold is exceeded.…”
Section: Discussionmentioning
confidence: 99%